CORRUPTION AS A SOCIO-PSYCHOLOGICAL PROBLEM - Xamidov Mansurjon (Modern World Education: New Age Problems – New solutions, 2026)
This article examines corruption as a socio-psychological problem, focusing on the individual, social, and cultural factors that contribute to corrupt behavior. Corruption is analyzed not only as a legal or economic phenomenon but also as a manifestation of social norms, attitudes, and cognitive biases. The study explores psychological mechanisms such as moral disengagement, rationalization, conformity, and social influence, as well as the impact of institutional culture and social networks. Implications for prevention, ethical education, and policy interventions are discussed to address corruption at both individual and societal levels.